Surgical considerations in infant lung transplantation: Challenges and opportunities. Issue 1 (17th September 2020) - Costello, John P.; Carvajal, Horacio G.; Abarbanell, Aaron M.; Eghtesady, Pirooz; Nath, Dilip S.
Abstract : Lung transplantation is a crucial component in the treatment of end‐stage lung disease in infants. Traditionally, most lung transplants have been performed in older children and adults, resulting in a scarcity of data for infant patients. To address the challenges unique to this age group, novel strategies to provide the best preoperative, intraoperative, and postoperative care for these youngest patients are paramount. We review recent advances in bridge‐to‐transplantation therapy, including the use of a paracorporeal lung assist device, and differences in surgical technique, including bronchial artery revascularization, for incorporation into the overarching treatment strategy for infants undergoing lung transplantation. Abstract : The authors delineate an overarching treatment strategy for infants undergoing lung transplantation, covering bridge‐to‐transplant strategies and common surgical techniques while providing a video of en bloc double lung transplantation in an infant. See the video in the online supporting information.